Antioxidant and Antihyperglycemic Properties of Three Banana Cultivars (Musa spp.). (30th October 2016) - Adedayo, Bukola C.; Oboh, Ganiyu; Oyeleye, Sunday I.; Olasehinde, Tosin A.
Abstract : Background . This study sought to investigate the antioxidant and antihyperglycemic properties of Musa sapientum (Latundan banana) (MSL), Musa acuminata (Cavendish banana) (MAC), and Musa acuminate (Red Dacca) (MAR). Materials and Methods. The sugar, starch, amylose, and amylopectin contents and glycemic index (GI) of the three banana cultivars were determined. Furthermore, total phenol and vitamin C contents and α -amylase and α -glucosidase inhibitory effects of banana samples were also determined. Results . MAC and MAR had the highest starch, amylose, and amylopectin contents and estimated glycemic index (eGI) with no significant different while MSL had the lowest. Furthermore, MAR (1.07 mg GAE/g) had a higher total phenol content than MAC (0.94 mg GAE/g) and MSL (0.96 mg GAE/g), while there was no significant difference in the vitamin C content. Furthermore, MAR had the highest α -amylase (IC50 = 3.95 mg/mL) inhibitory activity while MAC had the least (IC50 = 4.27 mg/mL). Moreover, MAC and MAR inhibited glucosidase activity better than MSL (IC50 3.47 mg/mL). Conclusion . The low sugar, GI, amylose, and amylopectin contents of the three banana cultivars as well as their α -amylase and α -glucosidase inhibitory activities could be possible mechanisms and justification for their recommendation in the management of type-2 diabetes.